2004
DOI: 10.1029/2003jd004308
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Measurements of Pollution in the Troposphere (MOPITT) and in situ observations of CO based on a large‐scale feature sampled during TRACE‐P

Abstract: [1] During Transport and Chemical Evolution over the Pacific (TRACE-P), there were several opportunities to perform in situ sampling coincident with overpasses of the Measurements of Pollution in the Troposphere (MOPITT) instrument on board the EOS Terra satellite. This sampling consisted of in situ vertical profiles of CO by NASA's DC-8 aircraft intended to provide data useful for validating MOPITT observations of CO column. One particular profile conducted over the central North Pacific revealed a layer of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The data selection follows the criteria of the MOPITT data quality statement (http://www.acd.ucar.edu/mopitt/products.shtml, access: February 2010): data within 25° from the poles have been left out, as the weight of the a priori CO profile in the MOPITT retrievals increases toward the pole. Nighttime data may be biased and are not exploited [ Crawford et al , 2004]. We then averaged the retrievals at the 3.75° × 2.5° resolution of LMDz‐SACS at the orbit level, in order to reduce the effect of correlated errors between neighboring observations in the inversion system.…”
Section: Methodsmentioning
confidence: 99%
“…The data selection follows the criteria of the MOPITT data quality statement (http://www.acd.ucar.edu/mopitt/products.shtml, access: February 2010): data within 25° from the poles have been left out, as the weight of the a priori CO profile in the MOPITT retrievals increases toward the pole. Nighttime data may be biased and are not exploited [ Crawford et al , 2004]. We then averaged the retrievals at the 3.75° × 2.5° resolution of LMDz‐SACS at the orbit level, in order to reduce the effect of correlated errors between neighboring observations in the inversion system.…”
Section: Methodsmentioning
confidence: 99%
“…Asian influence during TRACE‐P was weakest in the SE quadrant, which lies south of the dominant outflow track. The observed layer of high methanol concentrations at 2–4 km altitude is from one single Hawaii‐Guam flight where the aircraft sampled repeatedly an Asian outflow plume that had traveled southward and subsided [ Crawford et al , 2004]. High CO concentrations (200 ppbv) were observed in that layer.…”
Section: Evaluation With Observationsmentioning
confidence: 99%
“…The decrease in thermal contrast also shifts the vertical sensitivity of the MOPITT instrument upward, reducing the ability to observe low altitudes where CO concentrations are highest. Crawford et al [2004] found that nighttime observations of CO by MOPITT over the Pacific were less variable than daytime observations, which they attributed to an increase in the sensitivity of the retrieval to surface emissivity at night. We choose to use the daytime overpasses only in the results that follow.…”
Section: Constraints On Co Sources From Mopitt Observationsmentioning
confidence: 99%